Inovasi Potensi Pangan Kacang Kedelai: Dari Olahan Produk Hingga Pemasaran Online - Pramono, Suryo Adi (Jurnal Atma Inovasia, 2021)
Indonesia has a wealth of beautiful natural resources that attract tourists, cultural diversity and varied food resources.   Indonesia has the potential for local food resources from various types of nuts that have the potential to add nutrients to daily food. The agricultural commodity that the author's team chose is soybeans because soybeans are one of the agricultural commodities produced in Pacarejo Village, our focus of location. The output of educational videos about product innovation and e-book is the starting material for writing this article. The output is expected to provide information about the importance of product innovation by utilizing food potential from soybeans supported by the use of technology and internet support for online marketing. The method of implementation is carried out online by using a qualitative approach based on the post-positivist philosophy to examine natural objects systematically. The data collected is virtually analyzed and narrated in detail so that it is easy to understand. The innovation of processed products made from soybeans is the focus of this paper, in addition to the use of digital marketing as a further support. The data used in this paper only uses secondary data types. The data search was conducted through the websites of Pacarejo Village and Gunungkidul Regency, journal articles and other materials on the internet. The production of Soybean Food Potential Innovation Video which is the basis of this paper, the group hopes, can also help the people of Pacarejo Village in utilizing the existing food potential by processing soybeans into several product variants. It is hoped that the processing of innovative processed soybean products can provide added value, increase income and increase people's welfare. Selling products with online marketing is expected to reach a wider target market that includes across regions and across time.Indonesia memiliki kekayaan sumber daya alam indah yang menarik wisatawan, keragaman budaya dan sumber daya pangan yang variatif. Indonesia memiliki potensi sumber daya pangan lokal dari berbagai jenis kacang – kacangan yang berpotensi untuk menambah zat gizi dalam pangan sehari-hari. Komoditas pertanian yang tim penulis pilih adalah kacang kedelai karena kacang kedelai termasuk salah satu komoditas pertanian yang dihasilkan Desa Pacarejo, fokus lokasi kami. Luaran video edukasi mengenai inovasi produk serta e-book menjadi bahan awal penulisan artikel ini. Luaran diharapkan dapat memberikan informasi mengenai pentingnya untuk berinovasi produk dengan pemanfaatan potensi pangan dari kacang-kacangan kedelai didukung oleh pemanfaatan teknologi dan dukungan internet bagi pemasaran online. Metode pelaksanaan dilakukan secara daring dengan menggunakan pendekatan kualitatif yang berlandaskan pada filsafat post-positivism untuk mencermati obyek alamiah dengan sistematis. Data yang dikumpulkan secara virtual dianalisis dan dinarasikan secara rinci agar mudah dipahami. Inovasi produk olahan berbahan kacang kedelai menjadi fokus tulisan ini, di samping pemanfaatan digital marketing sebagai pendukung lanjutan. Data yang digunakan dalam penulisan ini hanya menggunakan jenis data sekunder. Pencarian data dilakukan melalui website Desa Pacarejo dan Kabupaten Gunungkidul, artikel jurnal dan bahan lain di internet. Produksi Video Inovasi Potensi Pangan Kacang Kedelai yang mendasari tulisan ini, kelompok harap, dapat pula membantu masyarakat Desa Pacarejo dalam pemanfaatan potensi pangan yang ada dengan mengolah kedelai menjadi beberapa varian produk. Pengolahan produk-produk inovatif olahan kacang kedelai ini diharapkan dapat memberikan nilai tambah, meningkatkan pendapatan serta kesejahteraan masyarakat. Penjualan produk dengan pemasaran online diharapkan dapat menjangkau target pasar yang lebih luas yang mencakup lintas daerah dan lintas waktu.